2022
DOI: 10.1371/journal.pgph.0000290
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological review of confirmed Lassa fever cases during 2016–2018, in Plateau State, North Central Nigeria

Abstract: Lassa fever (LF) is endemic in West Africa and constitutes a significant public health concern due to its potential for epidemics and associated high mortality. The first reported case and management of Lassa fever in Plateau State occurred more than 50 years ago. We set out to undertake a three-year epidemiological review of LF cases in Plateau State, North Central Nigeria. This is a retrospective study of all confirmed LF cases in Plateau State between 2016 and 2018. Plateau state Lassa fever- Line list and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…Past papers have shown that these lineage regions are distinct due to different physical environmental barriers such as the Niger and Benue rivers restricting the movement of the reservoir populations (11,12). Gomerep et al have also suggested that differences in apparent severity by lineage region may also be attributable to variable health-seeking behaviours by area (44). Published estimates of LASV evolutionary rates are low and Klitting et al have also shown slow rates of LASV circulation with a weighted lineage dispersal velocity between 0.8 and 1.0 km/year (35) We only found 5 estimates of the incubation period which reflects the challenges in attributing likely exposure times due to the complex transmission dynamics and the multiple potential routes of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Past papers have shown that these lineage regions are distinct due to different physical environmental barriers such as the Niger and Benue rivers restricting the movement of the reservoir populations (11,12). Gomerep et al have also suggested that differences in apparent severity by lineage region may also be attributable to variable health-seeking behaviours by area (44). Published estimates of LASV evolutionary rates are low and Klitting et al have also shown slow rates of LASV circulation with a weighted lineage dispersal velocity between 0.8 and 1.0 km/year (35) We only found 5 estimates of the incubation period which reflects the challenges in attributing likely exposure times due to the complex transmission dynamics and the multiple potential routes of infection.…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, there has been a notable increase in con rmed LF cases in Ondo State, Nigeria. The reasons for this surge in LF cases are multifaceted and complex, including factors such as poor (12,13,14,15). Housing characteristics and domestic practices also in uence rodent density, potentially affecting LF transmission to humans [30].…”
Section: Predictors Of the Likelihood Of Con Rmed Lf Cases Among Ward...mentioning
confidence: 99%
“…Poor sanitation and waste management practices can serve as breeding grounds for rodents, increasing the risk of human exposure [9,10,11]. Social and cultural factors, such as traditional food storage practices and communal living arrangements, may also contribute to the clustering of cases in certain areas [12,13,14,15]. Limited access to healthcare services and delays in diagnosis and treatment can worsen the impact of the disease.…”
Section: Predictors Of the Likelihood Of Con Rmed Lf Cases Among Ward...mentioning
confidence: 99%
See 2 more Smart Citations